2017
DOI: 10.4240/wjgs.v9.i6.139
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the management of rectal cancer: No surgery, minimal surgery or minimally invasive surgery

Abstract: Over the last decade, with the acceptance of the need for improvements in the outcome of patients affected with rectal cancer, there has been a significant increase in the literature regarding treatment options available to patients affected by this disease. That treatment related decisions should be made at a high volume multidisciplinary tumor board, after pre-operative rectal magnetic resonance imaging and the importance of total mesorectal excision (TME) are accepted standard of care. More controversial is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 88 publications
0
26
0
Order By: Relevance
“…One common observer (author AT) delineated on both THUNDER and CLINIC cohorts. Observers (median experience, 4 years; range [1][2][3][4][5][6][7][8][9][10] were trained by a resident radiation oncologist to identify relevant normal and abnormal anatomical structures within the ADC maps. In addition, original CT scans with annotated lesions for all the patients were available to the observers, so that they could be guided in the delineations in the ADC maps.…”
Section: Gross Tumour Volume (Gtv) Delineationmentioning
confidence: 99%
See 1 more Smart Citation
“…One common observer (author AT) delineated on both THUNDER and CLINIC cohorts. Observers (median experience, 4 years; range [1][2][3][4][5][6][7][8][9][10] were trained by a resident radiation oncologist to identify relevant normal and abnormal anatomical structures within the ADC maps. In addition, original CT scans with annotated lesions for all the patients were available to the observers, so that they could be guided in the delineations in the ADC maps.…”
Section: Gross Tumour Volume (Gtv) Delineationmentioning
confidence: 99%
“…Neo-adjuvant chemoradiotherapy (NACRT) followed by total mesorectal excision (TME) is the accepted standard of care for locally advanced rectal cancer (LARC) due to conclusive evidence of superior clinical outcome [1][2][3][4][5]. However, TME is a highly invasive procedure leading to bowel and bladder complications, and its added value for "good responders" is currently being debated [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…1 The detection, staging and management of rectal cancer has evolved dramatically over the last 30 years, with improved surgical techniques, involvement of multidisciplinary cancer disease site groups, and the utilization of a multimodal approach to treatment. [2][3][4] During this time, there has been an improvement of outcomes in locoregional control and overall survival. 5,6 However, with the volume and pace of evidence being generated, there remains some uncertainty and controversy regarding several elements of care, including the optimal neoadjuvant protocol, use of local excision and utility of adjuvant systemic therapy.…”
mentioning
confidence: 99%
“…Multiple studies have demonstrated that increased distance from the anal verge, anterior, and lateral rectal wall locations are associated with an increased risk for peritoneal violation during TEM and TaTME. 17,[19][20][21][22] In these retrospective reviews, peritoneal violation was not associated with increased risk for short-term or long-term complications, or increased rate of local recurrence. 20 One study, which looked at 28 cases with peritoneal perforation during TEM for T1 to T2 cancers and noted two occurrences of local recurrence, despite nonradical resection in 21% of cases.…”
Section: Resultsmentioning
confidence: 72%
“…However, due to the infancy of TAMIS, the literature on complication rates specific for robotic TAMIS is still very limited. Multiple studies have demonstrated that increased distance from the anal verge, anterior, and lateral rectal wall locations are associated with an increased risk for peritoneal violation during TEM and TaTME . In these retrospective reviews, peritoneal violation was not associated with increased risk for short‐term or long‐term complications, or increased rate of local recurrence .…”
Section: Discussionmentioning
confidence: 85%